(untitled) (London Journal of Medical and Health Research, 2026)
The human cervix is a complex structure that undergoes extensive changes throughout pregnancy and parturition to support the fetus and facilitate its expulsion. Cervical insufficiency is defined as the inability of the cervix to retain fetus, in the absence of uterine contractions owing to a functional or structural defect1. The term “Cervical insufficiency” is now replaced by “cervical incompetence”. Epidemiologic studies suggest an approximate incidence of 0.5% in the general obstetric population and 8% in women with a history of previous mid-trimester miscarriages.